O papel do femvertising na criação de produto e coleção de moda para a marca Decade Studio - Ponzi, Rafaela Godoy (Universidade do Vale do Rio dos Sinos, 2023)
The proposed work starts from cultural changes and how they influence communication. The study aims to briefly discuss the female representation within femvertising, an alternative marketing tool, drawing a parallel between communication and the fashion system. In doing so, we seek to identify how the interaction between customers and jeans brands specialized in jeans occurs, emphasizing representativeness as a key pillar of communication, aiming for an authentic representation of real women. Therefore, the general objective is to create and produce a collection following the model of Decade Studio, a brand that has a unique modeling system and aims for the inclusion of real women in its communications, through an analysis of the brand, its communication, and the potential Brazilian consumer audience.
Keywords: Jeans; Comunicação; Femvertising; Decade Studio; Jeans; Communication; Femvertising; Decade Studio